Accessible art in healthcare facilities: exploring perspectives of healthcare art for visually impaired people - Palityka, Daryia; Chrysikou, Evangelia; Murtagh, Niamh (Frontiers in Medical Technology, 2023)
Introduction Art in healthcare facilities shows promising results in improving patients' health and well-being and, as such, meets the WHO's definition of health technology. Yet, it remains unclear if healthcare art equally benefits all users. Given the growing number of visually impaired people (VIP), it is valuable to determine whether healthcare art is accessible to VIP and to explore strategies for improving it. Methods This study employed a mixed methodology, which included (1) secondary research of 25 cases of healthcare art programmes to identify the presence of accessible art in healthcare facilities and the practices that influence it; (2) review of thirty-one Health Building Notes and four supplementary British guidelines on healthcare art to discover if the accessibility of art is required and identify which recommendations influence it; and (3) interview surveys of healthcare art practitioners from three London NHS Trusts to identify opportunities to increase arts accessibility. Results and discussion The evidence showed that healthcare art programmes were mostly inaccessible to VIP. Most healthcare art programmes did not involve VIP in the commissioning process and, thus, lacked procedures that could facilitate accessibility. There were not enough recommendations in the healthcare facility guidelines to support the accessibility of arts for VIP. The recommendations on artwork in healthcare facility guidelines could increase accessibility if particular conditions were met. Interviews with NHS trusts in London revealed numerous opportunities to improve arts accessibility for healthcare art programmes.